Geospatial Analysis of Land Use Change in Way Kuripan Watershed, Bandar Lampung City - Candra Hakim Van Rafi’i; Dyah Indriana Kusumastuti; Dwi Jokowinarno (International Conference on Engineering and Technology Development (ICETD), 2013)
The purpose of the study is to analyze land use and land cover change impact on Way Kuripan discharge. Six scenarios of land use and land cover changes at Way Kuripan watershed area of 53.54 km² was developed based on geospatial analysis with Geographic Information System. Peak discharge is calculated by using rational method. From the six scenarios simulation, scenarios 1, 2, 3, and 4 maintained the protected areas of 80.15%. Land use and land cover changes done by changing areas from vacant land and agricultural areas to be residential, industrial and government office areas. From the analysis, peak discharge of scenarios 1, 2, 3, and 4 change slightly which are between 11.19% and 23.46%. These results are in contrast to scenarios 5 and 6, in which scenario 5 keep the protected areas about 53.35% while in scenario 6 left the protected areas around 30%. Those protected areas changed into residential areas. The result showed that in scenario 5, the peak discharge changed about 66.29%. While in scenario 6, it changed about 107.19%. It can be concluded that the existence of protected areas in Way Kuripan Watershed was very important role to reduce the peak discharge values.